2017
DOI: 10.1056/nejmc1706292
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cardiovascular Disease in Type 1 and Type 2 Diabetes

Abstract: BACKGROUNDLong-term trends in excess risk of death and cardiovascular outcomes have not been extensively studied in persons with type 1 diabetes or type 2 diabetes. METHODSWe included patients registered in the Swedish National Diabetes Register from 1998 through 2012 and followed them through 2014. Trends in deaths and cardiovascular events were estimated with Cox regression and standardized incidence rates. For each patient, controls who were matched for age, sex, and county were randomly selected from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…A recent long-term follow-up of patients registered in the Swedish National Diabetes Register found no effect from improved management of established risk factors on hospitalizations for heart failure in patients with T1DM, whereas patients with T2DM had a greater event-rate reduction than their matched controls, suggesting that some processes contributing to heart failure risk are not addressed by current clinical care for patients with T1DM [ 9 ].…”
Section: Established Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent long-term follow-up of patients registered in the Swedish National Diabetes Register found no effect from improved management of established risk factors on hospitalizations for heart failure in patients with T1DM, whereas patients with T2DM had a greater event-rate reduction than their matched controls, suggesting that some processes contributing to heart failure risk are not addressed by current clinical care for patients with T1DM [ 9 ].…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…Improved management of traditional cardiovascular risk factors has led to remarkable improvements in survival, with a 29% reduction in the relative risk of death over a 10-year period [ 9 ], such that the overall relative risk for CVD is now 2.3 for men and 3.0 for women [ 10 ]. This relative risk was previously reported as being 3.6 in men and 7.7 in women [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a major complication of type 2 diabetes (T2D) and the leading cause of death [1, 2]. The incidence of acute myocardial infarction (AMI) is higher in T2D and [3] survival after incident event is remarkably low [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms through which individuals develop type 1 and type 2 diabetes are different, both conditions are characterized by elevated blood glucose levels and share a similar elevated risk of cardiovascular mortality (1). Despite the fact that benefits from intensive glucose-lowering treatment were obvious in reducing microvascular complications in initial trials such as the Diabetes Control and Complications Trial (DCCT) (type 1 diabetes), the Action to Control Cardiovascular Risk in Diabetes (ACCORD) and Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trials (type 2 diabetes) showed no obvious benefit from glucose lowering treatment in the short term (2).…”
Section: Introductionmentioning
confidence: 99%